Potencial imunológico e expressão gênica de lectinas em camarões Penaeus vannamei cultivados em águas oligohalinas e desafiados com o Vírus da Mionecrose Infecciosa (IMNV) - Viana, Jhonatas Teixeira (2023)
Shrimp farming is one of the sectors of aquaculture that has grown the most in recent years, with notable focus on the species Penaeus vannamei. However, shrimp farming is impacted by diseases of the most diverse etiologies, including viral pathogens, as is the case of infectious myonecrosis (IMN), which has affected Brazilian shrimp farming since the early 2000s. Many researchers, observing the needs of shrimp farming, propose studies on the immunology of animals, in order to better undestand the mechanisms of the organism’s response to situations of immunological stress. In this context, we can highlight lectins, proteins with affinity for carbohydrates and glycoproteins. Due to their structural characteristics, lectins are capable of recognizing specific pathogens through interaction with molecular patterns, acting in different recognition and signaling pathways for the elimination of microorganisms. The present work aimed, primarly, to evaluate the differential gene expression of five immunological lectins (LvLdlrCTL, LvCTL4, LvCTL5, LvAV and LvCTLU) in P. vannamei shrimp experimentally infected with the infectious myonecrosis virus (IMNV), in order to understand the functioning of the shrimp’s immune system and the role of lectins in this process. The developed experiment evaluated the differential expression between shrimp infected and not infected by IMNV (50 µL, 104 copies of IMNV/µL), using samples from the hepatopancreas, gills, intestine and hemolymph. The animals were sampled at intervals of 0, 4, 8, 12, 24, 48, 72 and 96 hours post injection (hpi), in order to evaluate the differential expression along time in different tissues, using the β-actin and EF-1α genes as normalizers. Added to this, we employed bioinformatics analysis to characterize and elucidate probable structural and biochemical aspects related to immunological activities; and the total hemocytes count, to relate the action of lectins with possible cellular effects. It was observed that each lectin has a unique expression profile, which is also different for each analyzed tissue. Hepatopancreas and gills were considered the best tissues to evaluate the differential expression of immunological lectins, with LvLdlrCTL and LvCTL5 being the lectins with the most significatn results. LvLdlrCTL had its expression upregulated around 28 times and possibly the presence of low-density lipoprotein receptor domain and the abundance of post-translational modifications are involved in this process. LvCTL5, on the other hand, showed overlapping expression peaks with most of the other lectins analyzed, as well as in the belief that it has hemocytes recruiting action and immunoregulatory activity in immunological cascades. To, we conclude that the immunological lectins in P. vannamei act during IMNV infections, mainly LvLdlrCTL and LvCTL5, having their expression. regulated especially in the hepatopancreas and gills. The results also suggest that these lectins act in immunoregulation and hemocytes recruitment pathways; and, probably, the structural aspects of LvLdlrCTL favor its immunological action.